Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Wanita pada Sektor Informal di Kelurahan Sesetan, Kecamatan Denpasar Selatan - Anggi Harba Pramaysti; Ni Luh Karmini (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Economic development stems not only from the formal sector but also from the informal sector, with workers often transitioning to the latter due to factors such as their capabilities and characteristics, even if wages may be lower. This study aims to analyze the impact of age, hours worked, education level, and family dependents on women's income in the informal sector in Sesetan Village, South Denpasar District. The research was conducted in Sesetan Village, South Denpasar District, with a sample size of 90 female workers in the informal sector determined using the Slovin formula. This research method uses non-probability sampling with accidental sampling and purposive sampling techniques. Data collection was carried out through observation, structured interviews and in-depth interviews. The data analysis technique used is multiple linear regression analysis. Based on the research results, it can be seen that simultaneously, age, working hours, education level, and number of dependents have a significant effect on women's income in the informal sector in Sesetan Village, South Denpasar District. Partially, age has effect negative and significant on women's income in the informal sector in Sesetan Village, South Denpasar District, while working hours, education level, and number of dependents partially have a positive and significant effect on women's income in the informal sector in Sesetan Village, South Denpasar District. This research reveals the influence of age, working hours, education, and family dependents on women's income in the informal sector, providing theoretical and practical implications and becoming a reference for further research.